Relationship between Age, Hypertension, and Type-2 Diabetes Mellitus in Benign Prostatic Hyperplasia Patients with Erectile Dysfunction - Rabbani, Ahmad Zahid; Satyagraha, Paksi; Irnandi, Dicky Faizal (Universitas Airlangga, 2023)
Based on epidemiological data, the incidence of ED and BPH increases with the same risk factors, such as age, metabolic disease, and others. Aim: This study aimed to determine the prevalence of ED and its relationship to age and the presence of hypertension (HT) and type-2 diabetes mellitus (T2DM) comorbid in BPH patients. This is a cross-sectional study conducted at RSUD Dr. Saiful Anwar and Hermina Hospital Tangku-banprahu Malang utilizes two questionnaires, including the translated version of The Interna-tional Index of Erectile Function (IIEF-5) and Erectile Hardness Score (EHS) in Indonesian. There were 44 research subjects with only 21 respondents to the IIEF-5 question-naire, while the EHS questionnaire was given to all subjects. The prevalence of ED was found to reach 100.0% at the age of 70-79 years through the IIEF-5 questionnaire and aged ³ 80 years through the EHS questionnaire. The prevalence of ED in BPH patients with HT was found to be higher than non-HT patients through both questionnaires. The prevalence of ED in BPH patients with T2DM was found to be higher through the IIEF-5 questionnaire and slight-ly lower through the EHS questionnaire than non-T2DM patients. Age had a significant rela-tionship with ED through the EHS questionnaire (p = 0.006), while no significant relationship was found through the IIEF-5 questionnaire (p = 1.000). HT and T2DM did not have a signif-icant relationship with ED (IIEF-5: p = 0.229 and 0.526; EHS: p = 0.518 and 1.000). The prevalence of ED in BPH patients increases with age and the presence of comorbid HT and T2DM. Even so, there was no significant relationship between HT and T2DM with ED in BPH patients. A significant relationship between age and ED was only found in the EHS questionnaire but not in the IIEF-5 questionnaire.